An econometric analysis of the demand surge effect - David Döhrmann; Marc Gürtler; Martin Hibbeln (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2013)
In case of a natural catastrophe there is an increased demand for skilled labor and materials which in turn leads to significant price increases that should be taken into account in the forecast of catastrophe losses. Such price effects are referred to as Demand Surge effects. The paper at hand presents an extensive econometric analysis and modeling of the Demand Surge effect. We find that Demand Surge is positively influenced by the total amount of repair work, by alternative catastrophes in the same region in close temporal proximity, and by a higher amount of insurance claims per event. Furthermore, the Demand Surge effect is more pronounced if the construction sector is in a growth stage. In contrast, a higher capacity of the construction sector has a restraining effect on Demand Surge. In addition, if we restrict the data to very severe catastrophes, we observe a saturation effect according to which a wage increase for building services before a catastrophe reduces the Demand Surge effect.
Keywords: D45; J2; J31; Q54; R15; R23; R32; 330; demand surge; natural disasters; empirical analysis; insurance